Cleavage of Kv2.1 by BACE1 decreases potassium current and reduces neuronal apoptosis. (May 2022) - Sun, Qianwen; Liu, Fuchen; Zhao, Juan; Wang, Pin; Sun, Xiulian
Abstract: As an aspartic protease, β-site APP cleaving enzyme 1 (BACE1) can efficiently cleave amyloid precursor protein (APP) to produce amyloid beta (Aβ), a chief constituent of senile plaques in Alzheimer's disease. Thus, BACE1 inhibitor is identified as a therapeutic candidate for AD. However, recent failures of clinical trials using BACE1 inhibitors emphasized that comprehensively understanding of BACE1 function is particularly important. Kv2.1, a potassium channel, modulates potassium current in cortical neurons and potassium efflux is a requisite event in the process of cell apoptosis. Previously we showed that BACE2 cleaves Kv2.1 and reduces neuronal apoptosis. Our study here showed that BACE1 cleaves Kv2.1, and results in decreased Ik of Kv2.1. Furthermore, we demonstrated that the BACE1-cleaved Kv2.1 reduces neuronal apoptosis and BACE1 inhibitor markedly increases neuronal apoptosis. Our work indicates that BACE1 plays a neuroprotective role to reduce potassium efflux by cleavage of Kv2.1, implying inhibition of BACE1 may be neurotoxic. Graphical abstract: Image 1 Highlights: Kv2.1 modulates potassium current in cortical neurons and potassium efflux is a requisite event in the process of cell apoptosis. BACE1 cleaved Kv2.1 at three sites at its C-terminus. The BACE1-cleaved Kv2.1 reduces neuronal apoptosis and BACE1 inhibitor markedly increases neuronal apoptosis. BACE1 plays a neuroprotective role to reduce potassium efflux by cleavage of Kv2.1, implying inhibition of BACE1 may be neurotoxic.